Sustainable management of fall armyworm, Spodoptera frugiperda (J.E. Smith): challenges and proposed solutions from an African perspective - Nyamutukwa, S.; Mvumi, B.M.; Chinwada, P. (Informa UK Limited, 2024)
Fall armyworm (FAW), Spodoptera frugiperda, is threatening food security in Africa and thus sustainable management strategies are required. The pest has spread to over 44 countries in Africa since its first detection in 2016, causing maize yield losses valued at between US$2,531 and US$6,312 million per annum. Owing to FAW’s damaging potential, many untested management strategies, including those of doubtful efficacy, are being used by smallholder farmers in Africa. We analysed existing and emerging FAW management strategies on the continent. Research and training has focussed on FAW identification, scouting, digital monitoring tools, pest distribution, natural enemy database, and FAW impact on crops. Gaps identified include lack of clear national policies and regulations, FAW identification challenges, absence of reliable and sustainable management options, and FAW insecticide resistance development. Conservation of FAW natural enemies could enhance sustainable natural control. Farmer Field Schools and mass rearing of natural enemies for augmentative release are sustainable FAW control strategies. The “push-pull” strategy in controlling FAW has potential in Africa. Existing policies and regulations to facilitate better FAW management are discussed.